Cytokine production by monocytes, neutrophils, and dendritic cells is hampered by long-term intensive training in elite swimmers - Morgado, J. M.; Rama, L.; Silva, I.; de Jesus Inacio, M.; Henriques, A.; Laranjeira, P.; Pedreiro, S.; Rosado, F.; Alves, F.; Gleeson, M. (European Journal of Applied Physiology, 2012)
Elite level athletes seem to be prone to illness especially during heavy training phases. The aim of this study was to investigate the influence of long term intensive training on the functional features of innate immune cells from high competitive level swimmers, particularly the production of inflammatory mediators and the possible relationship with upper respiratory symptoms (URS) occurrence. A group of 18 swimmers and 11 healthy non athletes was studied. Peripheral blood samples were collected from athletes after 36 h of resting recovery from exercise at four times during the training season and at three times from non athletes. Samples were incubated in the presence or absence of LPS and IFN-? and the frequency of cytokine-producing cells and the amount produced per cell were evaluated by flow cytometry. In addition, plasma cortisol levels were measured and URS recorded through daily logs. The athletes, but not the controls, showed a decrease in the number of monocytes, neutrophils, and dendritic cell (DC) subsets and in the amount of IL-1ß, IL-6, IL-12, TNF-a, and MIP-1ß produced after stimulation, over the training season. Differences were most noticeable between the first and second blood collections (initial increase in training volume). Athlete`s cortisol plasma levels partially correlated with training intensity and could help explain the reduced in vitro cell response to stimulation. Our results support the idea that long-term intensive training may affect the function of innate immune cells, reducing their capacity to respond to acute challenges, possibly contributing to an elevated risk of infection.